THE EFFECT OF DYNAMIC CAPABILITIES ON ORGANIZATION RESILIENCE WITH MEDIATION OF DIGITAL TRANSFORMATION: A COMPARISON - Tjahjono, Monica Candra; Purbiyati, Yuliana Sri (International Journal of Economics, Business and Accounting Research (IJEBAR), 2023)
Dynamic capabilities are a topic that is currently hotly discussed and attracting attention. There is a lot of research involving dynamic capabilities and their effects on various things. This research compares two studies regarding the effects of dynamic capabilities on organizational resilience with the intervening variable digital transformation. The data used was taken from two articles that examined the same object using different respondents and produced different findings. The two articles were compared to find out why they had different results or findings. The results obtained are that human resources are required to be prepared in using digital transformation and respondents who understand the subject under study. Thus, in selecting respondents, criteria are needed that meet the requirements in order to get the right respondents